Multi‐Institutional Retrospective Analysis of Prognostic Scoring Systems for Dogs With Acute Pancreatitis (504 Dogs) - Harry Cridge; Daniela Cabrera; Timothy Bolton; Cameron Vaughn; Nolie Parnell; Betty Chow; Alexander Schreiber; Andrew Mackin; Paige Albers; Sichao Wang (Journal of Veterinary Internal Medicine)
ABSTRACT Background Acute pancreatitis (AP) in dogs has a broad clinical presentation and variable progression, making prognostication challenging. Hypothesis/Objectives (i) To compare predicted prognosis for death and for prolonged (≥ 5 days) hospitalization across scoring schemes for AP in dogs and (ii) to predict concordance of each scoring scheme with death and for prolonged hospitalization. Animals Five hundred four client‐owned dogs. Methods Multi‐institutional retrospective study. Data extracted from medical records included: signalment, history, physical examination findings, diagnostic results, length of hospitalization, and death. Five prognostic schemes (OS, CSI, APPLEfull, CAPS, MCAI) were calculated for each dog. Results Overall concordance was low. Only APPLEfull (p = 0.004) and MCAI (p = 0.01) scores were significantly different between survivors and non‐survivors. Overall, APPLEfull had the greatest concordance (0.632, 95% CI: 0.592–0.672) with length of hospitalization. Of the other more pancreatitis‐specific schemes, MCAI had the greatest concordance (0.576, 95% CI: 0.567–0.635) with length of hospitalization, while CSI had the lowest concordance with length of hospitalization (0.525, 95% CI: 0.494–0.556). Conclusions and Clinical Importance On a population level, APPLEfull and MCAI had the greatest predictive discrimination between dogs of normal and prolonged hospitalization. If an individual dog has any of the 5 prognostic score schemes above the proposed cut‐off for death, it should be interpreted with caution because of the low case fatality rate.